Breast cancer - an existential or an aesthetic crisis? A qualitative Analysis of the brest reconstruction decision making - Anna Brandt (Kazimierz Wielki University, 2017)
Breast reconstruction is part of a comprehensive approach to treating breast cancer. The basic contraindication is confirmed generalization of the disease. The purpose of breast reconstruction is primarily to improve the quality of life and to minimize the sense of grief and the fear of accepting the partner's body as a result of a resection of the gland. The aim of the study was to investigate the motivation of women to undergo reconstructive surgery. An interview was conducted with fourteen women after a mastectomy: seven women after breast reconstruction (two followed by a simultaneous reconstruction - simultaneously with a mastectomy) seven with no reconstruction (including one who had opted for the procedure and had a fixed date of three Women who are in the process of deciding to undergo surgery, the woman who has considered the decision to reconstructive surgery, but eventually resigned, two women who had abandoned the decision to reconstruct the breast from the beginning). In view of the results obtained, the purpose of breast reconstruction surgery is primarily to improve the quality of life and to minimize the sense of injury and fears associated with body acceptance after mastectomy. Women who do not make decisions explain this with fear of pain or disease progression. Among the reasons there are also the advanced age and the fact that reconstruction can be considered a manifestation of vanity.